2018
DOI: 10.1016/j.foodchem.2017.12.034
|View full text |Cite
|
Sign up to set email alerts
|

16-O-methylcafestol is present in ground roast Arabica coffees: Implications for authenticity testing

Abstract: HighlightsLipophilic extracts of ground roast Arabica coffees were authenticated by benchtop NMR.Small amounts of esterified 16-O-methylcafestol were found in Arabica coffees.The compound identity was confirmed by NMR and MS experiments.16-OMC remains a useful marker for non-Arabicas as these contain much higher amounts.6 out of 60 retail Arabicas contained significant amounts of non-Arabica species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 27 publications
4
53
1
Order By: Relevance
“…The discrimination between 16-OMC and 16-OMK cannot be achieved using NMR methods, 14 and then, both the quantification of In order to perform preliminary 16-OMK quantification, we investigated a green Arabusta coffee sample. Due to the pedigree of this interspecific coffee hybrid, a reasonably high content of 16-OMD may be expected, also in view of reported data.…”
Section: -Omk Detection and Preliminary Quantificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The discrimination between 16-OMC and 16-OMK cannot be achieved using NMR methods, 14 and then, both the quantification of In order to perform preliminary 16-OMK quantification, we investigated a green Arabusta coffee sample. Due to the pedigree of this interspecific coffee hybrid, a reasonably high content of 16-OMD may be expected, also in view of reported data.…”
Section: -Omk Detection and Preliminary Quantificationmentioning
confidence: 99%
“…Due to the pedigree of this interspecific coffee hybrid, a reasonably high content of 16-OMD may be expected, also in view of reported data. 14,22,23 In this case, the amount determined in a few Arabica samples analyzed so far. 24,25 Moreover, 1641 ± 164 mg/kg is the reported average 16-OMC content found in a wide range of green Robusta commercial samples, 7 and this value is within the wider range from 600 to 1800 mg/kg reported by Belitz et al, 26 which include the Arabusta 16-OMD content reported in the literature.…”
Section: -Omk Detection and Preliminary Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This large variability unfortunately prevents the use of 16‐OMC to quantify C. canephora in unknown roasted coffee blends. With the same aim, in contrast with previous studies, Gunning et al highlighted the concomitant presence of 16‐OMC and 16‐OMK (16‐O‐methyl kahweol) in both arabica and robusta, due to a peak at 3.16 ppm in the 1 H NMR spectra, thanks to an improved sample preparation procedure. In the present study, the lipophilic fraction was obtained by extracting 10 g of ground sample with 30 ml of chloroform and stirring at 600 rpm for 5 min.…”
Section: Application Of Nmr‐based Metabolomics In Food Science and Aumentioning
confidence: 99%
“…The unsaponifiable matter from Robusta presents cafestol and 16-O-methylcafestol as the two main components but the latter is stable during the roasting process. 16-O-methylcafestol has been considered a good chemical marker for detecting Robusta in coffee blends [2] for a long time until than it was detected also in Arabica roasted coffee [3]. However, the presence in Arabica of 16-O-methylcafestol in trace amounts makes this compound still a very useful chemical marker for authentication purposes.…”
Section: Introductionmentioning
confidence: 99%